PENGARUH DEBT COVENANT, TUNNELING INCENTIVE DAN FIRM SIZE TERHADAP KEPUTUSAN PERUSAHAAN MELAKUKAN TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR - Andani, Mega; Saputra, Indra; Hikmayanti, Hikmayanti (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
Abstract, The aim of this research is to examine the influence of the debt covenant, tunneling incentive, and firm size on the company's decision to conduct transfer pricing in manufacturing companies. This research uses quantitative methods. The research population consists of manufacturing companies listed on the Indonesian stock exchange in 2019–2022. The research sample used a purposive sampling technique with a total sample of 11 companies. Logistic regression analysis is used in this research. The results of this research show that company size influences the company's decision to carry out transfer pricing, while the debt covenant and tunneling incentive do not influence the company's decision to carry out transfer pricing in manufacturing companies.